Microstructure and toughness characterization of AA6061 hybrid composite reinforced with eucalyptus ash, periwinkle shell, and plantain fiber - Obinna O. Barah; Kennedy C. Onyelowe; Stephen N. Nnamchi; Milon D. Selvam (Discover Applied Sciences)
Abstract This study presents the development and evaluation of AA6061 hybrid composites reinforced with plantain fiber ash (PFA), eucalyptus wood ash (EWA), and periwinkle shell powder (PSP) to enhance mechanical properties while promoting sustainable manufacturing practices. Hybrid composites were fabricated with varying reinforcement ratios and characterized using advanced techniques such as scanning electron microscopy (SEM–EDS) and Fourier-transform infrared spectroscopy (FTIR). Mechanical properties, including hardness and wear resistance, were assessed under standardized conditions. The optimal composition, comprising 5% PSP, 3% EWA, and 2.5% PFA, demonstrated a 224% increase in hardness compared to the base AA6061 alloy. FTIR analyses confirmed the synergistic integration of organic and inorganic components, contributing to enhanced thermal stability and corrosion resistance. These findings underscore the potential of agro-marine waste reinforcements in advancing eco-friendly, high-performance engineering materials. This work highlights the feasibility of using sustainable reinforcements to improve tribological and mechanical performance, paving the way for innovative applications in industries such as aerospace, automotive, and construction.